Visualization of Intraaneurysmal Flow Patterns with Transluminal Flow Images of 3D MR Angiograms in Conjunction with Aneurysmal Configurations - Satoh, Toru; Onoda, Keisuke; Tsuchimoto, Shoji (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: How the complex flow phenomena generated within unruptured cerebral aneurysms relate to the corresponding aneurysmal geometry is unknown. To estimate the interaction between flow patterns and morphologic features of unruptured cerebral aneurysms, we developed a method to visualize intraanuerysmal flow patterns with transluminal flow imaging of 3D MR angiograms in conjunction with aneurysmal configurations.METHODS: Transluminal images of the vessel lumen were reconstructed with use of a parallel volume-rendering algorithm by selecting information on the margin of lumina from the volume data sets of 3D time-of-flight MR angiograms. Transluminal flow images were then created by superimposing flow-related intraluminal information onto transluminal images. Intraaneurysmal flow patterns were evaluated in three cases of unruptured cerebral aneurysms, based on the animated display of transluminal flow images with stepwise extracted intraluminal volume data of signal intensity, in conjunction with the corresponding aneurysmal configurations depicted on 3D MR angiograms.RESULTS: Transluminal flow images showed 3D visualization of flow-related signal intensity distribution obtained from volume data of MR angiograms, so that qualitative information regarding intraaneurysmal flow patterns could be estimated with respect to morphologic features of cerebral aneurysms.CONCLUSION: Transluminal flow images of 3D MR angiograms allowed feasible visualization of intraaneurysmal flow patterns that were studied. More work is required to validate the technique and clarify the significance of being able to visualize intraaneurysmal flow patterns.